2014
DOI: 10.5455/msm.2014.26.12-16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Hypertensive Crises in Emergency Medical Services

Abstract: Objectives:The objective of this study is to evaluate the incidence and clinical presentation of hypertensive crises in the Emergency medical services of the Community Health Centre “Dr. Mustafa Šehović” Tuzla in relation to age, sex, duration and severity of hypertension, as well as the prevalence of accompanying symptoms and clinical manifestations.Methods:The study was conducted between November 2009 and April 2010 and included 180 subjects of both sexes, aged 30-80 with a diagnosis of arterial hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…The HC can be classified as hypertensive emergency or hypertensive urgency depending on the end-organ involvement, including renal, cardiac and neurologic injury [ 8 , 9 ]. From the estimation, it is reported that approximately 1% of the patients with hypertension develop hypertensive crisis at some point during their life span, however, men are approximately affected two times more frequently than women [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HC can be classified as hypertensive emergency or hypertensive urgency depending on the end-organ involvement, including renal, cardiac and neurologic injury [ 8 , 9 ]. From the estimation, it is reported that approximately 1% of the patients with hypertension develop hypertensive crisis at some point during their life span, however, men are approximately affected two times more frequently than women [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas one study showed low absorption of captopril from the sublingual cavity of rabbits, some others found no difference in proportion of BP decrease, plasma rennin activity inhibition, and ACE inhibition (9,12,19). On the other hand, many studies found that sublingual captopril's decrease of blood pressure is better than the oral method (20)(21)(22).…”
Section: Discussionmentioning
confidence: 95%
“…Hypertensive crisis is characterized by a sudden onset of increased BP and represents more than 25% of all medical urgencies/emergencies, often threatening patients' lives (12). Because different treatment approaches are required, drawing a line between hypertensive emergency and urgency is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although headaches and dizziness were both found to be common in adults presenting to the emergency department with hypertensive crisis, they were equally common in a control group with uncomplicated hypertension. 103 In children, there may be a stronger association between hypertensive crisis and dizziness. 104 Patients with intracranial hypotension following LP or spontaneous CSF leak may also present with auditory or vestibular symptoms, including acute vertigo.…”
Section: Disorders Of Intracranial Pressure and Brain Edemamentioning
confidence: 99%